(untitled) (PANGEEA, 2025)
This paper was exclusively thought of as a case study in the field of soil erosion assessment, aiming at creating a correct GIS-based methodology for a former coal quarry (Vărzari), located in the NE part of Romania, in Bihor County. Thus, it is attempted a combination of both traditional methods (Universal Soil Loss Equation) and the new means of analysis enabled by the new technology, i.e. Geographic Information System (GIS). This study aims at carefully analyzing the present situation of soil erosion in the Vărzari Coal-Quarry. The main outcomes of this study are thematic maps (i.e. landslide prediction map, flow direction map, soil erosion map) viewed as tools for planners and policy-makers at local and regional level.